2010
DOI: 10.1083/jcb1892oia7
|View full text |Cite
|
Sign up to set email alerts
|

P2X4 receptors in activated C8-B4 cells of cerebellar microglial origin

Abstract: We investigated the properties and regulation of P2X receptors in immortalized C8-B4 cells of cerebellar microglial origin. Resting C8-B4 cells expressed virtually no functional P2X receptors, but largely increased functional expression of P2X4 receptors within 2-6 h of entering the activated state. Using real-time polymerase chain reaction, we found that P2X4 transcripts were increased during the activated state by 2.4-fold, but this increase was not reflected by a parallel increase in total P2X4 proteins. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 61 publications
(118 reference statements)
1
8
0
Order By: Relevance
“…However, despite numerous attempts, P2X4R‐evoked currents could not be detected in microglia 48h after induction of SE. Activity of P2X4R is tightly regulated by a balance between rapid, activity‐dependent endocytosis, and membrane insertion of the protein (Qureshi et al, ; Toulme et al, ). The large amount of ATP released during slice processing is likely to promote the rapid endocytosis of P2X4R, precluding the recording of its activity in acute brain slices.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite numerous attempts, P2X4R‐evoked currents could not be detected in microglia 48h after induction of SE. Activity of P2X4R is tightly regulated by a balance between rapid, activity‐dependent endocytosis, and membrane insertion of the protein (Qureshi et al, ; Toulme et al, ). The large amount of ATP released during slice processing is likely to promote the rapid endocytosis of P2X4R, precluding the recording of its activity in acute brain slices.…”
Section: Discussionmentioning
confidence: 99%
“…For reverse transcriptase (RT)-polymerase chain reaction (PCR), first strand cDNA was synthesized (Amersham Biosciences, NJ) and amplified by PCR using specific primers as described (Ploix et al 2001; Schmid et al 2009). Real-time PCR was performed using the iQ5 real-time PCR detection system (Bio-Rad) and primer sequences described in (Noor et al 2010; Toulme et al 2010). The relative number of CCL21 transcripts per hypoxanthine phosphoribosyl transferase (HPRT) transcripts was determined by using calibration standards for both HPRT and CCL21 as previously described (Toulme et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR was performed using the iQ5 real-time PCR detection system (Bio-Rad) and primer sequences described in (Noor et al 2010; Toulme et al 2010). The relative number of CCL21 transcripts per hypoxanthine phosphoribosyl transferase (HPRT) transcripts was determined by using calibration standards for both HPRT and CCL21 as previously described (Toulme et al 2010). Briefly, PCR fragments served as standards for calibration of quantitative PCR were purified from preparative gels with an extraction kit (QiAquick; Qiagen Germany).…”
Section: Methodsmentioning
confidence: 99%
“…However, in a subsequent study, amitriptyline was found to have no effect at recombinant human P2X4 receptors and to act as a noncompetitive antagonist at recombinant rat and mouse P2X4 receptors 59. Interestingly, one group did find an inhibitory effect of tricyclic antidepressants and serotonin uptake inhibitors on native P2X4 receptors in mouse cerebellar microglia,60 but they concluded that this was due to inhibition of trafficking of the P2X4 receptors to the plasma membrane, rather than antagonism of the receptor per se .…”
Section: P2x4 Receptorsmentioning
confidence: 96%